Anterolateral Extraarticular Stabilisation of the Knee: Modified Lemaire Procedure - Giebel, Gregor M.; Ahmad, Sufian S.; Stöckle, Ulrich; Konrads, Christian (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
The anterolateral aspect of the knee is prone to laxity or symptomatic instability, if the anterior cruciate ligament (ACL) is torn. It is necessary to address this issue in patients with general joint hyperlaxity, overextension of the knee, massive anterolateral instability, or re-tear of the ACL with chronic instability. In these cases, and in addition to a preoperative bony workup and revision ACL reconstruction, anterolateral stabilisation should be considered to avoid persistent anterolateral rotation instability and failure of the ACL reconstruction.To stabilise the anterolateral corner of the knee, the modified Lemaire procedure as presented and illustrated here is a straight forward surgical technique that can be performed right after standard ACL reconstruction surgery, if indicated. It is independent from the graft choice for the ACL reconstruction, and the surgical setting in the operating room remains unchanged.
Keywords: ALL; vorderes Kreuzband; Knie; Ligament